Endocardial-Epicardial Phase Mapping of Prolonged Persistent Atrial Fibrillation Recordings: High Prevalence of Dissociated Activation Patterns. (August 2020) - Parameswaran, Ramanathan; Kalman, Jonathan M.; Royse, Alistair; Goldblatt, John; Larobina, Marco; Watts, Troy; Walters, Tomos E.; Nalliah, Chrishan J.; Wong, Geoffrey; Al-Kaisey, Ahmed; Douglas Anderson, Robert; Voskoboinik, Aleksandr; et al.
Abstract : Background: Endocardial-epicardial dissociation and focal breakthroughs in humans with atrial fibrillation (AF) have been recently demonstrated using activation mapping of short 10-second AF segments. In the current study, we used simultaneous endo-epi phase mapping to characterize endo-epi activation patterns on long segments of human persistent AF. Methods: Simultaneous intraoperative mapping of endo- and epicardial lateral right atrium wall was performed in patients with persistent AF using 2 high-density grid catheters (16 electrodes, 3 mm spacing). Filtered unipolar and bipolar electrograms of continuous 2-minute AF recordings and electrodes locations were exported for phase analyses. We defined endocardial-epicardial dissociation as phase difference of ≥20 ms between paired endo-epi electrodes. Wavefronts were classified as rotations, single wavefronts, focal waves, or disorganized activity as per standard criteria. Endo-Epi wavefront patterns were simultaneously compared on dynamic phase maps. Complex fractionated electrograms were defined as bipolar electrograms with ≥5 directional changes occupying at least 70% of sample duration. Results: Fourteen patients with persistent AF undergoing cardiac surgery were included. Endocardial-epicardial dissociation was seen in 50.3% of phase maps with significant temporal heterogeneity. Disorganized activity (Endo: 41.3% versus Epi: 46.8%, P =0.0194) and single wavefronts (Endo: 31.3% versus Epi: 28.1%, P =0.129) were the dominant patterns. Transient rotations (Endo: 22% versus Epi: 19.2%, P =0.169; mean duration: 590±140 ms) and nonsustained focal waves (Endo: 1.2% versus Epi: 1.6%, P =0.669) were also observed. Apparent transmural migration of rotational activations (n=6) from the epi- to the endocardium was seen in 2 patients. Electrogram fractionation was significantly higher in the epicardium than endocardium (61.2% versus 51.6%, P <0.0001). Conclusions: Simultaneous endo-epi phase mapping of prolonged human persistent AF recordings shows significant Endocardial-epicardial dissociation marked temporal heterogeneity, discordant and transitioning wavefronts patterns and complex fractionations. No sustained focal activity was observed. Such complex 3-dimensional interactions provide insight into why endocardial mapping alone may not fully characterize the AF mechanism and why endocardial ablation may not be sufficient. Abstract : Supplemental Digital Content is available in the text.